Hypoglycaemic, Hypolipidaemic and Antioxidant Properties of Celastrus paniculatus Seed Extract in STZ-induced Diabetic Rats - Md Fahim Ahmad; Md Ali Haidar; Nida Naseem; Haseeb Ahsan; Waseem Ahmad Siddiqui (Molecular and Cellular Biomedical Sciences, 2023)
Background: Celastrus paniculatus is a herb used in the Ayurvedic system of medicine that has been reported to show multiple pharmacological properties. In this study, we explored the antioxidative, hypolipidaemic and hypoglycaemic potential of C. paniculatus methanolic seed extract (CPMSE) in high-fat diet (HFD)/streptozotocin (STZ)-induced type 2 diabetes mellitus (T2DM) rats.Materials and methods: Seeds of C. paniculatus were extracted in methanol using Soxhlet extraction method. A total of 36 rats were induced with STZ and HFD and treated with glibenclamide or various concentrations of CPMSE. Upon treatment, blood samples were collected and kidney and liver samples were homogenised. Serum biochemical estimation was performed using several diagnostic kits. Protein was estimated by bicinchoninic acid (BCA) method. Oxidative stress was assessed by measuring malondialdehyde level and superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST) activity.Results: CPMSE caused improvements in glucose homeostasis, lipid profile, liver function and oxidative stress parameters in a dose-dependent manner. CPMSE significantly decreased the levels of fasting blood glucose and glycated haemoglobin as well as increased insulin level and total protein content. There was an increase in total cholesterol (TC), low density lipoprotein-cholesterol (LDL-C), triglycerides (TG) levels and reduction in high density lipoprotein-cholesterol (HDL-C) level. There was a decrease in serum levels of serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT) and alkaline phosphatase (ALP). CPMSE decreased LPO and increased CAT, SOD and GST activity.Conclusion: CPMSE has hypoglycaemic, hypolipidaemic and antioxidant properties by reducing the oxidative stress.Keywords: diabetes mellitus, Celastrus paniculatus, antioxidant, phytochemicals, phytonutrients, streptozotocin, high-fat diet